The Employee Turnover Phenomenon in Saudi Arabia’s Private Schools: Case Study - Alsoaery, Abdulrahman (Advances in Social Sciences Research Journal, 2023)
This article represent an investigation of the causes behind high turnover of teachers in Saudi Arabian private schools and recommends ways and means to reduce its incidence. It is widely acknowledged that school teachers play a critical role in providing high quality education, so inadequacy, unavailability, or high turnover among teachers can radically affect the quality of education provided by schools and furthermore have negative outcomes for children. This research makes use of an elaborate literature review on various aspects of labour turnover, with specific regard to turnover among teachers, and follows the case study method for researching the subject issue. The study focuses on the Private Education Group, which runs a number of private schools in Saudi Arabia. The research makes use of qualitative analysis and the administration of semi- structured interviews. The research reveals low salaries to be the most important reason for staff turnover among the teachers and the existence of significant differences in attitudes between employees and officials. And finally, the researcher has made a number of recommendations for improving retention of teachers in private schools in Saudi Arabia.